2022
DOI: 10.1159/000524953
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Caregivers Working in Nursing Homes during the COVID-19 Pandemic

Abstract: <b><i>Introduction:</i></b> There have been numerous reports of cluster outbreaks of coronavirus disease 2019 (COVID-19) in hospitals and nursing homes. Healthcare workers fighting COVID-19 experience mental health issues. Caregivers in nursing homes experienced increased psychological distress and concern about deterioration of their mental health. We conducted a large-scale web-based survey exploring mental health among caregivers working in nursing homes during the COVID-19 pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
(50 reference statements)
2
5
0
Order By: Relevance
“…Nurses were also associated with higher depressive symptoms when controlling for covariates. These results were consistent with previous studies [ 36 , 37 , 38 ]. However, multiple logistic regression analysis controlling for the influence of various sociodemographic variables showed that only being a nurse was associated with higher depressive symptoms.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Nurses were also associated with higher depressive symptoms when controlling for covariates. These results were consistent with previous studies [ 36 , 37 , 38 ]. However, multiple logistic regression analysis controlling for the influence of various sociodemographic variables showed that only being a nurse was associated with higher depressive symptoms.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, the association with depressive symptoms disappeared for among nursing home staff and PCR-positive testing. Among HCWs, nurses could be at high risk of mental disorders due to their primary duties, including direct care for patients at high risk of COVID-19 [ 37 ]. Meanwhile, as PCR-positive HCWs responded to the screening test soon after and during the quarantine, the association between testing PCR-positive and depressive symptoms might have disappeared after being relieved from hard work.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses and nursing home staff were also associated with higher depressive symptoms when controlling for covariates. These results were consistent with previous studies [34][35][36]. However, multiple regression analysis controlling for the influence of various sociodemographic variables showed that only being nurses and being nursing home staff were associated with higher depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Among HCWs, nurses and nursing home staff could be at high risk of mental disorders due to their primary duties, including direct care for patients at high risk of COVID-19 [35].…”
Section: Discussionmentioning
confidence: 99%
“…HCWs who fought COVID-19 in long-term care facilities experienced a dramatic increase in mental health issues as well. They were exposed to high levels of stress and were at high risk for developing severe depressive symptoms and burnout [ 12 , 13 ]. Major depressive symptoms are associated with an increased risk of believing common misinformation about COVID-19 vaccines, which might correlate with vaccination readiness [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%